Coexistence of Juvenile Systemic Lupus Erythematosus and Juvenile Spondyloarthropathy: A Case Report and Review of the Literature - Ayşe TANATAR; Ummihan TOPAL; Şerife GÜL KARADAĞ; Hafize Emine SÖNMEZ; Nuray AKTAY AYAZ (Archives of Rheumatology, 2020)
Sacroiliitis has been scarcely reported in patients with systemic lupus erythematosus (SLE). In this article, we presented a pediatric case with coexis- tence of juvenile SLE and juvenile spondyloarthropathy (SpA) and discussed the clinical and laboratory findings by the literature review. A 16-year- old female patient with a diagnosis of SLE was referred to our outpatient clinic with inflammatory low-back pain for two months. Sacroiliac magnetic resonance imaging confirmed the presence of bilateral active sacroiliitis. She was finally diagnosed with juvenile SpA. She achieved remission with subcutaneous methotrexate and non-steroid anti-inflammatory drugs. To the best of our knowledge, this is the first pediatric case with SLE and SpA. This case provides further implication about atypical presentation of a well-known disorder.